"I made you bear a son, and you shall call his name Mena!" The Saint, the Egg, and Medieval Nubia - Agata Deptuła (Vox Patrum)
This article examines the Old Nubian Miracle of St Menas, preserved in the British Library Ms. Or. 6805, as a unique testimony to Christian traditions in medieval Nubia. While sharing certain motifs with earlier miracles known from Coptic, Greek, and Arabic sources, this text presents a distinctive narrative absent in other traditions. The article is structured around two main sections: the historical and cultural context of medieval Nubia and a detailed analysis of the miracle, focusing on its connections to other Menas traditions. The analysis employs a comparative method, juxtaposing the Old Nubian text with earlier textual sources. Material evidence, including paintings and inscriptions, is also incorporated to contextualize the miracle within broader Nubian Christian practices. The text, either translated into Old Nubian or partially composed in this language, references symbols and concepts familiar to a local Nubian audience.